THE USE OF ANIMATION VIDEOS TO IMPROVE STUDENT’S SPEAKING ABILITY AT SMP NEGERI 8 SATAP TONDANO - Losung, Nadya Maghladena Indri; Mogea, Tini; Liando, Nihta V. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Education is an important foundation for every individual and even the country. In today’s life, especially in the era of technology, education has become greatly helped by the existence of various kinds of technological media that can support the education process. Therefore, innovation in learning is needed, English learning innovation can be done by applying the use of learning media that can help students in absorbing information better to increase student interest in learning. The purpose of the study is to measure the influence of Audio-Visual as a Learning Media. Using class action research, this study employs a quantitative descriptive analytic technique. The number of samples in this study were 16 grade VIII students of SMP Negeri 8 SATAP Tondano who had been involved in the use of animation videos to improve student’s speaking ability. The results showed that the eighth grade students of SMP Negeri 8 SATAP Tondano liked the use of animation video as a learning media for learning English, especially to improve the speaking ability. Therefore, it is hoped that Animation Videos can be a reference for learning media to learn English, especially to improve the speaking ability.